2021
DOI: 10.1007/s11356-021-16551-1
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, a double-edged sword for the environment: a review on the impacts of COVID-19 on the environment

Abstract: This review paper discusses the most relevant impacts of the COVID-19 pandemic on the environment. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) originated in Wuhan, China, in December 2019. The disease has infected 70 million people and caused the death of 1.58 million people since the US Food and Drug Administration issued an Emergency Use Authorization to develop a vaccine to prevent COVID-19 on December 11, 2020. COVID-19 is a global crisis that has impacted everything directly connected wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 91 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…Setti et al (2020) found that the initial spread of COVID-19 was significantly associated with daily PM10 exceedances in Italy. However, despite the positive environmental changes observed, many studies have reported that the COVID-19 pandemic has impacts on the environment (Alalawi et al, 2022;Abedin et al, 2022;Miyah et al, 2022;Atoufi et al, 2021;Shakil et al, 2020). Public health policies adopted by governments during the pandemic are expected to influence future legal and policy frameworks to protect marine and terrestrial ecosystems from the adverse effects of humaninduced pollution.…”
Section: Discussionmentioning
confidence: 99%
“…Setti et al (2020) found that the initial spread of COVID-19 was significantly associated with daily PM10 exceedances in Italy. However, despite the positive environmental changes observed, many studies have reported that the COVID-19 pandemic has impacts on the environment (Alalawi et al, 2022;Abedin et al, 2022;Miyah et al, 2022;Atoufi et al, 2021;Shakil et al, 2020). Public health policies adopted by governments during the pandemic are expected to influence future legal and policy frameworks to protect marine and terrestrial ecosystems from the adverse effects of humaninduced pollution.…”
Section: Discussionmentioning
confidence: 99%
“…Air quality improved significantly during lockdowns. At the same time, the increased demand for personal protective equipment and the mishandling of their disposal caused increased microplastic pollution of water and soil (Atoufi et al , 2021). The benefits of a decreased need for fossil energy resources and decreased air pollution are, however, vanishing, as the activity of industries and societies returns to normal (Madurai Elavarasan et al , 2021).…”
Section: Literature Review: Covid-19 Impact On Sustainable Developmen...mentioning
confidence: 99%
“…However, the forced behavioral changes simply modified the nature and distribution of pollution sources, without necessarily reducing their intensity [3,4]. Consequently, despite a diffuse public interpretation, often spread by the media, considering only the occurred changes as positive, the evidence derived from observations is different and requires further investigations [5,6].…”
Section: Introductionmentioning
confidence: 99%